EFEKTIVITAS TEKNIK KONTRAK PERILAKU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI RUMAH PADA MASA PANDEMI COVID-19 - Tiara Maharani; Rochani Rochani; Raudah Zaimah Dalimunthe (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2021)
This study aims to determine the effectiveness of the behavioral contract technique in increasing students' learning motivation at home during the Covid-19 pandemic. The method used in this study is a quantitative method. While the research technique used is a quasi-experimental design with the type of Nonequivalent Control Group Design. 3. Based on the results of the study, it was found that there was a change in the pre-test and post-test scores in the experimental group and the control group. This can be seen in the average values: 1) Experimental class: with a mean difference of 41. 2) Control class: with a mean difference of 1.2. Normality test using Kolmogrov Smirnov. Based on the results of the normality test, it can be seen that sig. 0.05, then the data is normally distributed. Furthermore, for the posttest homogeneity test the experimental and control groups with levene statistic got 0.063 results, based on the homogeneity test results 0.000 <0.05 then homogeneous. Furthermore, data processing on the hypothesis test is the t test, from the results of the t test processing the data taken is the equal variance assumed score. In the sig (2-tailed) data obtained 0.010 where sig (2-tailed) < 0.05 then Ha is accepted and Ho is rejected. It can be concluded that in decision making, namely Ha is accepted, the behavioral contract technique is effective in increasing the learning motivation of students of SMK PGRI 1 Serang City Class X at home during the Covid-1 pandemic.